2006
DOI: 10.3892/ijmm.18.1.41
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 inhibitors sensitize human hepatocellular carcinoma cells to TRAIL-induced apoptosis

Abstract: Cyclooxygenase (COX)-2 is upregulated in a variety of human cancers, including in hepatocellular carcinoma (HCC), whereas it is undetectable in most normal tissue. Evidence suggests that COX-2 is likely to be involved in hepatocarcinogenesis and, thus, COX-2 may be involved in an early process in carcinogenesis, dedifferentiation. To address this possibility, we investigated the effect of COX-2 inhibitors on TNF-related apoptosis, inducing ligand (TRAIL) sensitivity and its molecular mechanisms, with special a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 24 publications
4
22
1
1
Order By: Relevance
“…However, our previous report (31) showed that Fas, a molecule in the death-receptor extrinsic pathway, was upregulated by meloxicam, suggesting the extrinsic pathway might also participate in the apoptosis induced by meloxicam. In addition, the caspase-independent pathways might be also involved in COX-2-inhibition-induced apoptosis, as Yamanaka et al (45) reported that selective COX-2 inhibitors NS398 and CAY10404 induced apoptosis of human HCC SK-Hep1 cells by upregulating TRAIL receptors and downregulating survivin.…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous report (31) showed that Fas, a molecule in the death-receptor extrinsic pathway, was upregulated by meloxicam, suggesting the extrinsic pathway might also participate in the apoptosis induced by meloxicam. In addition, the caspase-independent pathways might be also involved in COX-2-inhibition-induced apoptosis, as Yamanaka et al (45) reported that selective COX-2 inhibitors NS398 and CAY10404 induced apoptosis of human HCC SK-Hep1 cells by upregulating TRAIL receptors and downregulating survivin.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies have shown that the apoptotic inhibitors of cIAP2 and survivin are important factors in determining the apoptosis of HCC cells (3,14). Thus, we investigated the expression of the two proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, findings of recent studies (3,12,13,30) have shown that many targeted drugs alter their characteristics by acting on special targets. In the present study, we found that silencing SNAIL can increase the expression of p53, which alters the sensitization of HCC cells to TRAIL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these factors is the oncogene c-myc, which is known to be a positive regulator of cyclin D1 and PCNA transcription (Daksis et al, 1994). C-myc also regulates the expressions of bcl-2 and survivin in hepatic cancer cells (Yamanaka et al, 2006). However, the relation of c-myc and bcl-2, survivin was not still fully clear.…”
Section: Discussionmentioning
confidence: 99%